Formal Methods: State of the Art and New Directions - Boca, Paul.; Bowen, Jonathan P.; Siddiqi, Jawed; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2010)
The last decade has witnessed a modest but sustained increase in researching and applying formal methods. A number of well cited success stories are now available and provide strong evidence that formal methods can be effective and deployed in industrial-scale applications. Through fundamental contributions from leading researchers, this book provides further evidence of the use of formal methods in the areas of requirements, design, modelling and implementation, verification and validation. The self-contained chapters are views from experts in these areas, providing readers with rich background information and a diverse breadth of specialist material. This authoritative collection of views provides a snapshot of the field and will be of considerable interest to researchers and professionals seeking a perspective on fundamental underpinnings of formal methods and current hot topics in the field. The website www.fmsand.info is a useful resource, providing material associated with the book and links to further related information.
Domain Engineering -- Program Verification and System Dependability -- The Abstract State Machines Method for High-Level System Design and Analysis -- Applications and Methodology of ?Z -- The Computer Ate My Vote -- Formal Methods for Biochemical Signalling Pathways -- Separation Logic and Concurrency -- Programming Language Description Languages.
Keywords: Computer science; Software engineering; Computer Science; Software Engineering; Mathematical Logic and Formal Languages; Programming Languages, Compilers, Interpreters